Knockdown of glycine decarboxylase complex alters photorespiratory carbon isotope fractionation in Oryza sativa leaves - Giuliani, Rita; Karki, Shanta; Covshoff, Sarah; Lin, Hsiang-Chun; Coe, Robert A.; Koteyeva, Nuria K.; Quick, W. Paul; von Caemmerer, Susanne; Furbank, Robert T.; Hibberd, Julian M.; Edwards, Gerald E.; Cousins, Asaph B. (Oxford University Press, 2019)
The influence of reduced glycine decarboxylase complex (GDC) activity on leaf atmosphere CO2 and (CO2)-C-13 exchange was tested in transgenic Oryza sativa with the GDC H-subunit knocked down in leaf mesophyll cells. Leaf measurements on transgenic gdch knockdown and wild-type plants were carried out in the light under photorespiratory and low photorespiratory conditions (i.e. 18.4 kPa and 1.84 kPa atmospheric O-2 partial pressure, respectively), and in the dark. Under approximately current ambient O-2 partial pressure (18.4 kPa pO(2)), the gdch knockdown plants showed an expected photorespiratory-deficient phenotype, with lower leaf net CO2 assimilation rates (A) than the wild-type. Additionally, under these conditions, the gdch knockdown plants had greater leaf net discrimination against (CO2)-C-13 (Delta(o)) than the wild-type. This difference in Delta(o) was in part due to lower C-13 photorespiratory fractionation (f) ascribed to alternative decarboxylation of photorespiratory intermediates. Furthermore, the leaf dark respiration rate (R-d) was enhanced and the (CO2)-C-13 composition of respired CO2 (delta C-13(Rd)) showed a tendency to be more depleted in the gdch knockdown plants. These changes in R-d and delta C-13(Rd) were due to the amount and carbon isotopic composition of substrates available for dark respiration. These results demonstrate that impairment of the photorespiratory pathway affects leaf (CO2)-C-13 exchange, particularly the C-13 decarboxylation fractionation associated with photorespiration